Drift motion of charged particle in wave field of magnetic pumping under Сherenkov and cyclotron resonance conditions - Yeliseyev, Yu.N.; Stepanov, K.N. (Вопросы атомной науки и техники, 2013)
The charged particle motion problem in electromagnetic field of magnetic pumping under Chrenkov and cyclotron resonance conditions is solved in drift approximation. The wave field is produced by alternating surface azimuthal current, modeling the current of solenoidal antenna, which use is considered within the frames of a developed ICR-method of isotope separation. The drift motion equations are derived and their three first integrals are found at arbitrary values of Larmor radius. It is shown that the increasing of a particle Larmor radius involves the increasing of radius of the Larmor center, i.e. involves drift of heated particles to plasma edge. During Larmor gyration these ions transit near to a system axis. В дрейфовом приближении решена задача о движении заряженной частицы в поле волны магнитной накачки в условиях черенковского и циклотронного резонансов. Поле волны создается поверхностным переменным азимутальным током, моделирующим ток соленоидальной антенны, использование которой рассматривается в рамках разрабатываемого ИЦР-метода разделения элементов и изотопов. Выведены уравнения дрейфового движения, справедливые при произвольной величине ларморовского радиуса, и найдены три их первых интеграла. Показано, что увеличение ларморовского радиуса частицы под действием волны накачки сопровождается увеличением радиуса ее ларморовского центра, т.е. дрейфом нагретых частиц на периферию плазмы. При ларморовском вращении эти ионы проходят вблизи оси системы. У дрейфовому наближенні вирішено задачу про рух зарядженої частки в полі хвилі магнітного накачування в умовах черенковського й циклотронного резонансів. Поле хвилі створюється поверхневим змінним азимутальним струмом, що моделює струм соленоїдальної антени, використання якої розглядається в рамках розроблюваного ІЦР-методу розділення елементів і ізотопів. Виведені рівняння дрейфового руху справедливі при довільній величині ларморовського радіуса, і знайдено три їх перших інтеграла. Показано, що збільшення ларморовського радіуса частки під дією хвилі накачування супроводжується збільшенням радіуса її ларморовського центра, тобто дрейфом нагрітих часток на периферію плазми. При ларморовському обертанні ці іони проходять поблизу осі системи.